A rate adaptive bit-loading algorithm for in-building power-line communications based on DMT-modulated systems - Morosi, S.; Marabissi, D.; Enrico Del Re; Fantacci, R.; Del Santo, N. (IEEE transactions on power delivery, 2006)
This paper deals with a variable rate discrete multitone modulation system for broadband power-line communications, based on the bit-loading algorithm proposed by Leke and Cioffi. In the proposed system a suitable least mean square channel estimator is considered, which is based on the insertion of a training sequence (TS). The proposed approach will be compared with the ideal channel estimates, showing its effectiveness. Moreover, different TS lengths will be compared. The system performance, expressed in terms of bit rate and bit-error rate, is derived by simulation with and without estimation errors. The propagation environment has been assumed as a frequency-selective multipath fading channel with additive colored Gaussian noise, according to the in-building networks model